Spatial distribution of tree species composition and carbon stock in Tozi tropical dry forest, Sinnar State, Sudan - EMAD HASsAN ELAWAD YASIN; BUDI MULYANA (Society for Indonesian Biodiversity, 2022)
Abstract. Yasin EHE, Mulyana B. 2022. Spatial distribution of tree species composition and carbon stock in Tozi tropical dry forest, Sinnar State, Sudan. Biodiversitas 23: 2359-2368. Dryland forest ecosystem in Sudan plays an important role, either ecologically or economically, for the community around the forest areas. However, land-use change, illegal logging and grazing have caused dryland forests in the country to degrade. The research aimed to investigate the species composition and carbon stock in a Tozi tropical dry forest (TTDF), a typical dryland forest ecosystem in Sinnar state, Sudan. A total of 306 circular sample plots (1000 m2 for each) were established using a systematic sampling grid method. The distance between plots was 400 m and between survey lines 500 m. In each plot, all living trees were identified and counted, and their diameter at the breast height (DBH) was recorded. Research findings showed that there were 2,339 individual trees representing four species (Acacia seyal, Balanites aegyptiaca, Acacia senegal and Acacia mellifera) that belong to two families. The B. aegyptiaca and A. seyal were the dominant species widely distributed in the TTDF. The average tree density was 175 trees/ha and the Shannon-Weiner index for trees diversity was 0.264. For the seedlings stage, A. mellifera showed a high value of frequency and density, followed by B. aegyptiaca and A. seyal. The structure of seedlings, saplings, and adults trees formed a reverse J-shape in which the density of seedlings was the highest and followed by saplings and adult trees. Carbon stock of A. seyal, B. aegyptiaca, A. senegal, and A. mellifera were 990.95, 2602.78, 1085.82, and 249.20 kg C/ha, respectively. Spatial analysis showed that sites composed of three species resulted in the highest above ground carbon stock compared to single species, two species, and four species compositions.